Torana (entrance) at the Mahalaxmi Temple - Ghosh, Ayan (2023)
The Mahalaxmi Temple, marked by its framed torana (marble arch), is the newest temple in the precinct of Banganga Tank. It was built on the site of a shrine at the base of a peepal tree located in the northeast corner of the tank. It was built in 1973, by members of the Shrimali Brahmin community from Rajasthan. The temple has been refurbished in 2021.